Alterations in the gut microbiota of patients with silica-induced pulmonary fibrosis - Yao Zhou (Journal of Occupational Medicine and Toxicology, 2019)
Abstract Silicosis resulting from silica exposure is a global occupational disease characterized by severe pathological changes in progressive pulmonary fibrosis. Previous evidence has indicated that dysbiosis of the gut microbiota occurs after environmental dust exposure and is associated with certain diseases. The aims of this study are to elucidate the compositional and functional characteristics of the gut microbiota in early-stage silicosis and to understand their influence on pulmonary fibrosis. We investigated the gut microbial composition of fecal samples from 18 patients and 21 healthy subjects using 16S rRNA gene sequencing technology. Compared with the healthy subjects, reductions in the levels of Firmicutes and Actinobacteria were noted in patients with silicosis and progressive pulmonary fibrosis, as well as lower levels of Devosia, Clostridiales, AlloprevotellaandRikenellaceae_RC9. Lachnospiraceae and Lachnoclostridium levels were increased in patients with silicosis. GOC and KEGG analyses were used to predict that certain bacteria taxa play critical roles in the development of pulmonary fibrosis, including posttranslational modification, amino acid transport and metabolism, nucleotide transport and metabolism, and ribosomal structure and biogenesis. KEGG analysis showed that certain taxa participate in various roles including cancer, endocrine metabolism, immune system, signaling molecules and interaction, and transcription. Collectively, in this pilot study, microbiota changes have been represented in the gut of patients with silicosis. Although this change in gut microbiota have been represented, caution is needed when interpreting the findings since this is observational finding, not necessarily causative. More studies should be performed in the expanding population to be verified and more studies underlying biological mechanisms for better understanding the relationship between gut microbiota and development of pulmonary fibrosis in patients with silicosis.